Business digital maturity in Europe and its implication for open innovation - Magdalena Tutak; Jarosław Brodny (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This paper presents the results of a study aimed at assessing the level of business digital maturity in Europe and at analyzing similarities between companies in terms of implemented Industry 4.0 technologies. The digital transformation of production and service enterprises has become a common direction of development for all economic sectors. The very idea of Industry 4.0 has become synonymous with innovation and is the basis for business development. The role and importance of these transformations are also recognized by the EU which has been promoting and supporting the development of an innovative digital economy for many years. However, individual EU countries differ in terms of digital business maturity due to the implementation of Industry 4.0 technology. The article addresses this problem by presenting the results of a comprehensive study of the implementation of Industry 4.0 digital technologies in enterprises in the EU-27 countries and by assessing similarities between these countries in terms of these technologies. The similarity analysis was carried out using the k-means method. The Gini coefficient and Lorenz curves were utilized to determine the unevenness of the implementation of these technologies in individual countries, and the Weighted Aggregated Sum Product Assessment method was used to assess the level of digital maturity. The research was based on eight selected determinants (indicators) that characterize the most important technologies related to Industry 4.0. The results showed high diversity among EU countries in terms of digital maturity. Scandinavian countries (Finland and Denmark) and Malta were found to be leaders in this area, while the weakest results were reported for Greece, Romania, Bulgaria, Hungary, and Latvia. The findings provide a lot of new information about the current state of development of the digital economy in EU countries, which should be used in both the development and implementation of new solutions related to economic digitalization policy in this region.
Keywords: 650; digital maturity; enterprises; European Union countries; Industry 4.0